Biopolymer nanocomposites with customized mechanical property and exceptionally antibacterial performance. (20th October 2020) - Bai, Huiyu; Liang, Zhenzhen; Wang, Dawei; Guo, Jiaqi; Zhang, Shengwen; Ma, Piming; Dong, Weifu
Abstract: Biopolymer nanocomposite integrated antibacterial property with customized mechanical property is attractive for food packaging industry, biomedical and tissue engineering. Herein, we demonstrate one facile approach to engineer biopolymer nanocomposite with customized mechanical property and exceptional antibacterial activity. Customization of the mechanical property of polyvinyl alcohol (PVA)-based nanocomposite is achieved by tuning the ratio of cellulose nanocrystal (CNC) and graphene oxide (GO). We investigated the water resistance and water vapor barrier properties of the engineered PVA/CNC/GO nanocomposites. Biopolymer nanocomposite is capable to undergo softening under higher relative humidity (98% RH) and shows extraordinary ductility. The inclusion of silver nanoparticles (Ag NPs) by in-situ reduction of silver nitrate modulates the mechanical property of ready-made PVA/CNC/GO nanocomposite and improves water resistance and water vapor barrier. The antibacterial test demonstrates AgNP-loaded PVA/CNC/GO nanocomposite is endowed with an exceptional antibacterial capacity for both Gram-negative ( E. coli ) and Gram-positive ( S. aureus ) bacteria. The antibacterial durability test exhibits the AgNP-loaded PVA/CNC/GO nanocomposite maintain similar antibacterial capability after washing nanocomposite for 30 d. AgNP-loaded PVA/CNC/GO nanocomposite with customized mechanical property and extraordinary antibacterial activity will open new venues for material design in food packaging, biomedical and tissue engineering. Graphical abstract: Image 1